Odpowiedź :
Odpowiedź:
a) P = a * b
a = 2a + 3
b = 3b
P = 3b( 2a + 3) = 6ab + 9b
b)
[tex]p = \frac{(a + b) \times h}{2} [/tex]
a = 2a + 3
b = 3a + 5
h = 4a
[tex]p = \frac{(2a + 3 +3a + 5) \times 4a }{2} = \frac{(5a + 8) \times 4a}{2} = \frac{20 {a}^{2} + 32a }{2} = 10a {}^{2} + 16a[/tex]
a)
[tex]a \times b [/tex]
[tex](2a + 3 )\times 3b = 6ab + 9b[/tex]
b)
[tex] \frac{( a + b) \times h }{2} [/tex]
[tex] \frac{(3a + 5 + 2a + 3) \times 4a}{2} = \frac{(5a + 8) \times 4a}{2} = \frac{20 {a}^{2} + 32a }{2} = 10 {a}^{2} + 16a[/tex]